Prevalence of intestinal parasites in school-age children in Turkey: A systematic review and meta-analysis. - Ahmed Galip Halidi; Kemal Yaran; Selahattin Aydemir; Abdurrahman Ekici; Yusuf Dilbilir (PLoS Neglected Tropical Diseases)
Background Intestinal parasites are a major public health problem worldwide, especially in societies with low socioeconomic status and where sanitation rules are not sufficiently emphasized. School-age children are the most affected group in these societies. In light of the literature data, the intestinal parasites detected in school-age children and the geographical and socioeconomic structure of Turkey are evaluated together. The study hypothesizes that the parasite prevalence in school-age children is high, and there is substantial socioeconomic and geographical variation in species-specific prevalence. It is aimed to determine the pooled prevalence of intestinal parasite infections in school-age children in Turkey, identify the common parasite species, and compare the prevalence in different geographical regions of Turkey. Methods The Web of Science, PubMed, Scopus, and TR index databases were searched to access published articles reporting the presence of intestinal parasites among school-age children in Turkey. The prevalence of intestinal parasites was calculated using a random effects model. Subgroup analyses were performed according to the parasite species and geographical regions of Turkey. Also, year-based meta-regression analyses were conducted. Results A total of 204.754 samples from 99 articles were included in the analysis. The pooled prevalence of intestinal parasites was 29%, with high heterogeneity (I2 = 99.88%, P < 0.001). The subgroup analysis revealed that the Southeastern Anatolia is the region with higher prevalence of intestinal parasites among school-age children, with a rate of 41% (I2 = 99.44%, P < 0.001). Subgroup analysis for parasite species revealed that G. intestinalis/duedonalis/labmblia (11%; 95% CI: 9%-13%, I2 = 99.85) was the most frequently detected parasite in school-age children, followed by Blastocystis spp., Enterobius vermicularis, Entamoeba coli, Ascaris lumbricoides and Entamoeba histolytica/dispar. Conclusion The prevalence of intestinal parasitic infections (IPI) among school-age children in Turkey is particularly high in Southeastern Anatolia, the Mediterranean, and Eastern Anatolia. Socioeconomic conditions, education, and geography are the main factors that affect this situation. It is crucial for school-age children and their parents to receive education on the transmission mechanisms of intestinal parasitic infections (IPIs) and strategies for their prevention. Furthermore, it is essential for local governments and public authorities to upgrade infrastructure to ensure that drinking water and food are not contaminated by polluted water sources.